Designing Online Project Monitoring with a Design Thinking Approach at Telkom Indonesia's Government Solution Unit - Diati Levi Putri; Rina Djunita Pasaribu (International Journal of Economics, Business and Innovation Research, 2025)
As the era of globalization dev elops, influencing the growth of technology worldwide, especially in Indonesia, PT Telkom Indonesia, as a company engaged in the Information Technology sector, continues to strive to improve its services and meet the needs of its customers and provide customer satisfaction. In line with Telkom's main vision of becoming the preferred digital telco to advance society, Telkom continues to strive to transform into a digital telecommunication company. TelkomGroup implements a customer-oriented business and operational strategy that makes the company lean and agile in adapting to the rapidly changing telecommunications industry. In its transformation, Telkom offers products, services, and solutions by providing digital connectivity, digital platforms, and digital services to enterprise, government, and SME customers. In carrying out its function as a solution provider to government customers, the Government solution unit in the Solution Delivery & Assurance division has an internal challenge where the process of monitoring projects is still manual, using Google Sheets created by each sub-unit, so it cannot be monitored centrally and in real time. The purpose of this research is to design a solution dashboard for the government solution unit using design thinking. The design thinking stages used consist of five stages, namely empathize, define, ideate, prototype, and testing. The method used in this research is a qualitative research method, with the data collection method being interviews. The result of this research is a tested prototype that can display data for each government project handled by the government solution unit.